Effect of dietary selenium from selenium-enriched kale sprout, selenomethionine, and sodium selenite on performance and selenium concentrations in the tissues of growing quails - Anut Chantiratikul; Orawan Arunsangseesod; Eakapol Wangkahart; Kwanyuen Leamsamrong; Piyanete Chantiratikul (Animal Bioscience, 2021)
Objective This study aimed to determine the effect of dietary selenium (Se) from Se-enriched kale sprout (SeKS), selenomethionine (SeMet), and sodium selenite (SS) on performance, carcass characteristics and Se concentrations in the tissues, and to study the relationship between Se concentrations in muscle and feather in growing quails. Methods The 320 quails (7 d of age) were divided into four treatments, according to a completely randomized design. The treatments were T1: control diet; T2, T3, and T4: control diets plus 0.2 mg Se/kg from SS, SeMet, and SeKS, respectively. The performance, carcass characteristics, and Se concentrations in the tissues of quails were determined. Results The results indicated no effect (p>0.05) of Se supplementation on performance, carcass characteristics and glutathione peroxidase (GSH-Px) activity in breast muscle of quails. Supplemental Se from SS, SeMet, and SeKS increased greater (p<0.05) Se concentrations in breast muscle, liver, kidney, heart, and feather, compared to those of quails fed the control diet. Quails fed Se from SeMet had greater (p<0.05) Se concentrations in the tissues than quails fed Se from SeKS and SS. In addition, Se concentrations in breast muscle and feather of quails at 21 and 42-d-old were highly correlated (R2 0.714 to 0.756) (p<0.05). Conclusion Performance, carcass characteristics and GSH-Px activity in breast muscle of quails were not affected (p>0.05) by dietary Se supplementation. The Se from SeMet was more effective in increasing Se concentrations in the tissues of quails than Se from SeKS and SS. Feather Se concentrations of 21 and 42-d-old quails can be used for assessment of Se bioavailability of Se sources.